Efficient Aflatoxin B1 Sequestration by Yeast Cell Wall Extract and Hydrated Sodium Calcium Aluminosilicate Evaluated Using a Multimodal In-Vitro and Ex-Vivo Methodology - Alexandros Yiannikouris; Juha Apajalahti; Hannele Kettunen; Suvi Ojanperä; Andrew N. W. Bell; Jason D. Keegan; Colm A. Moran (Toxins, 2021)
In this work, adsorption of the carcinogenic mycotoxin aflatoxin B1 (AFB1) by two sequestrants—a yeast cell wall-based adsorbent (YCW) and a hydrated sodium calcium aluminosilicate (HSCAS)—was studied across four laboratory models: (1) an in vitro model from a reference method was employed to quantify the sorption capabilities of both sequestrants under buffer conditions at two pH values using liquid chromatography with fluorescence detection (LC-FLD); (2) in a second in vitro model, the influence of the upper gastrointestinal environment on the mycotoxin sorption capacity of the same two sequestrants was studied using a chronic AFB1 level commonly encountered in the field (10 µg/L and in the presence of feed); (3) the third model used a novel ex vivo approach to measure the absorption of 3H-labelled AFB1 in the intestinal tissue and the ability of the sequestrants to offset this process; and (4) a second previously developed ex vivo model readapted to AFB1 was used to measure the transfer of 3H-labelled AFB1 through live intestinal tissue, and the influence of sequestrants on its bioavailability by means of an Ussing chamber system. Despite some sorption effects caused by the feed itself studied in the second model, both in vitro models established that the adsorption capacity of both YCW and HSCAS is promoted at a low acidic pH. Ex vivo Models 3 and 4 showed that the same tested material formed a protective barrier on the epithelial mucosa and that they significantly reduced the transfer of AFB1 through live intestinal tissue. The results indicate that, by reducing the transmembrane transfer rate and reducing over 60% of the concentration of free AFB1, both products are able to significantly limit the bioavailability of AFB1. Moreover, there were limited differences between YCW and HSCAS in their sorption capacities. The inclusion of YCW in the dietary ration could have a positive influence in reducing AFB1′s physiological bioavailability.